The filmmaker's philosopher : Merab Mamardashvili and Russian cinema - DeBlasio, Alyssa (Edinburgh University Press : Edinburgh University Press ;, 2019)
Exploring Mamardashvili's extensive philosophical output, as well as a range of recent Russian films, Alyssa DeBlasio reveals the intellectual affinities amongst directors of the Mamardashvili generation - including Alexander Sokurov, Andrey Zvyagintsev and Alexei Balabanov.
Keywords: Mamardashvili, Merab.; Mamardashvili, Merab; Motion pictures -- Russia (Federation) -- History.; Philosophy in motion pictures.; Philosophie au cinéma.; HISTORY -- Europe -- Russia & the Former Soviet Union.; Motion pictures; Philosophy in motion pictures; Russia (Federation); History